Synthesis and properties of amino- and guanidino-peptoid peptide nucleic acids - Lu, Xiao Wei (2010)
Peptide nucleic acid (PNA) is a synthetic mimic of DNA and RNA that can bind to complementary DNA and RNA with high affinity and sequence specificity. The structural simplicity, high hybridization affinity and in vivo stability of PNA have made it an attractive agent for antigene and antisense applications in basic biology and medicine. However, the inherent limitations of PNA, such as low solubility and poor cell permeability, have greatly limited its use. Extensive modification work has been conducted on PNA in an effort to further improve its desirable properties and overcome its limitations. This thesis presents the results of a new type of PNA analogs with a peptoid-like side chain appending from the r-N of the PNA backbone. The side chain of varying lengths is further functionalized with a positively charged amino or guanidino group. An interesting relationship between the hybridization affinity of the resultant amino-peptoid PNA (AP-PNA) or guanidino-peptoid PNA (GP-PNA) and the length of the side chain is observed. This makes it possible to modulate the hybridization and pharmacological properties of PNA in a more predictable way. Chapter 1 of this thesis contains an introduction to peptide nucleic acid, their chemo-physical and biological properties as well as their applications. Information on PNA analogs with a chiral backbone is also provided. Chapter 2 pertains to the synthesis of AP-PNA monomers, AP-PNA oligomers and GP-PNA oligomers. The AP-PNA monomers of different side chain length (2, 3, 4, 5 or 6 carbon) were synthesized with the exocyclic amines of their four natural nucleobases protected by an acyl or Bhoc protecting group. The AP-PNA oligomers were synthesized on Rink amide PEGA resin using standard solid-phase Fmoc peptide synthesis protocols. The GP-PNA oligomers were achieved by converting the peptoidic amino group on AP-PNA to the corresponding guanidino-peptoid via a guanylation reaction. Other AP-PNA derivatives were obtained by acylating the amino group with interesting functional groups. Chapter 3 demonstrates the hybridization and cellular uptake properties of AP-PNA, GP-PNA and the side-chain amine-acylated AP-PNA derivatives.